Viscount-Norwich-Bulli schemes for banks, etc : best banking methods - Bulli, H.C. (New Delhi, India, 1976)
This scheme will help bankers to catch hold of forgers and impersonators, in the bank premises itself, and at the time of their attempt to utilize their forgeries, in all cases
Confidential
osc 22/05/2019
Arch
Keywords: Banking; India